Pharmacophore-based virtual screening and in silico investigations of small molecule library for discovery of human hepatic ketohexokinase inhibitors for the treatment of fructose metabolic disorders - Elsaman, Tilal; Mohamed, Magdi Awadalla; Elderdery, Abozer Y.; Alsrhani, Abdullah; Alzahrani, Badr; Ghanem, Heba Bassiony; Mills, Jeremy; Rayzah, Musaed; Alzerwi, Nasser A. N.; Al-sultan, Afnan; Idrees, Bandar; Rayzah, Fares (Frontiers in Pharmacology, 2025)
IntroductionExcessive fructose consumption is a significant driver of metabolic disorders, including obesity, diabetes, non-alcoholic fatty liver disease and non-alcoholic steatohepatitis primarily by promoting insulin resistance and fat accumulation. Ketohexokinase C (KHK-C), a pivotal enzyme in fructose metabolism, catalyzes the phosphorylation of fructose to fructose-1-phosphate, initiating a cascade of downstream metabolic processes. In contrast to glucose metabolism, KHK-C lacks negative feedback regulation, allowing the continuous phosphorylation of fructose, which leads to heightened levels of glucose, glycogen, and triglycerides in the bloodstream and liver. While targeting KHK-C offers a promising therapeutic avenue, no drugs have yet been approved for clinical use. Pfizer’s PF-06835919 has progressed to phase II trials, demonstrating a reduction in liver fat and improved insulin sensitivity, while Eli Lilly’s LY-3522348 also shows significant potential. Nonetheless, there remains a critical need for the development of novel KHK-C inhibitors that offer improved pharmacokinetics, enhanced efficacy, and superior safety profiles.MethodsIn the present study, a comprehensive computational strategy was employed to screen 460,000 compounds from the National Cancer Institute library for potential KHK-C inhibitors. Initially, pharmacophore-based virtual screening was used to identify potential hits, followed by multi-level molecular docking, binding free energy estimation, pharmacokinetic analysis, and molecular dynamics (MD) simulations to further evaluate the compounds. This multi-step approach aimed to identify compounds with strong binding affinity, favorable pharmacokinetic profiles, and high potential for efficacy as KHK-C inhibitors.ResultsTen compounds exhibited docking scores ranging from −7.79 to −9.10 kcal/mol, surpassing those of the compounds currently undergoing clinical trials, PF-06835919 (−7.768 kcal/mol) and LY-3522348 (−6.54 kcal/mol). Their calculated binding free energies ranged from −57.06 to −70.69 kcal/mol, further demonstrating their superiority over PF-06835919 (−56.71 kcal/mol) and LY-3522348 (−45.15 kcal/mol). ADMET profiling refined the selection to five compounds (1, 2, and 4–6), and molecular dynamics simulations identified compound 2 as the most stable and promising candidate compared to the clinical candidate PF-06835919.ConclusionThese findings highlight compound 2 as a potent KHK-C inhibitor with predicted pharmacokinetics and toxicity profiles supporting its potential for treating fructose-driven metabolic disorders, warranting further validation.